Genome sequence of Vibrio parahaemolyticus C5A causing acute hepatopancreatic necrosis disease in shrimp isolated from a Malaysian shrimp culture pond - Md. Ali, Amatul Samahah (Elsevier, 2022)
We report the complete genome sequence of Vibrio parahaemolyticus strain C5A causing an acute hepatopancreatic necrosis disease (AHPND) in Penaeus vannamei sampled from a culture pond in the east of peninsular Malaysia isolated in 2017.